Pregnancy outcomes in women with excessive gestational weight gain in Dschang health district of Cameroon - Nguefack, Skinner Lekelem; Ndenkeh, Jackson Jr; Bekolo, Cavin; Kenfack, Bruno (International Journal of Scientific Reports, 2021)
Background: Excessive gestational weight gain (EGWG) during pregnancy can lead to adverse outcomes for the mother and/or the new-born. The aim of the study was to determine the prevalence of EGWG as well as its effect on pregnancy outcomes amongst pregnant women at the health district of Dschang in Cameroon. Methods: This was a cross sectional study conducted from January to June 2019 and targeting all consenting pregnant women in Dschang District Hospital. They were administered a prepared questionnaire followed by their body mass index measurements for times at the beginning and the end of gestation to measure GWG. Logistic regression was used to determine the association of the EGWG to some particular pregnancy outcomes, adjusting for other factors with significance set at 5%. Results: A total of 400 women were included in this study with a mean age of 27±5years, 59.2% being married and 34.8% still being students. Also it was noted that 24.8% of these women were obese while 25.3% had EGWG. Furthermore, EGWG was independently associated to prolonged labour (aOR=2.4; CI: 1.3-4.6; p value=0.007), genital tract laceration (aOR=2.0; CI: 1.0-3.8; p value=0.036) and foetal macrosomia (aOR=7.3; CI: 3.5-15.2; p value<0.001). Conclusions: The prevalence of EGWG was high and it was associated with prolonged labour, genital tract laceration and foetal macrosomia. There is thus the need to improve the awareness of these women on EGWG as well as a constant follow up all through gestational period so as to regulate their GWG. The above measures will help to reduce occurrence of these complications, and consequently reduce maternal and neonatal mortality.